“Get Her for Me, for She Pleases Me Well” - Solomon Olusola Ademiluka (Old Testament Essays, 2024)
Judges 14 speaks to the Nigerian context on the role of parents in the marriage process. Unlike in the traditional African society where the choice of spouses was determined by parents and the family, in Nigeria today, parents have little involvement in their children’s choice of marriage partner. Applying narrative reading and the descriptive approach, the article examines this text in light of the significance of parents' role in choosing marriage partners among Nigerian Christians. The study finds that due to the influence of Christianity and modernisation, Nigerian parents now play little role in the choice of their children’s marriage partners and that this is one of the factors responsible for the rampant marriage failures in society. It concludes that to curb the high rate of marriage instability among Nigerian Christians, the church in Nigeria should review its marriage theology to emphasise the role of parents in mate selection, using the Samson story as a literary instrument.